Organizational policies for inclusion: practices of respect towards sexual and gender minorities (Research, Society and Development, 2020)
This paper presents and analyzes proposals of organizational policies for the insertion and permanence of sexual and gender minorities in the labor market. For this purpose, a bibliographic research on invisibility, marginalization and violence in labor relations involving LGBT+ people, as well as a quantitative research using a questionnaire answered based on availability and convenience, about their own previous knowledge on inclusion policies. 194 of the respondents considered themselves LGBT+, thus meeting the established criteria. Data were treated through statistical analysis and the majority of the respondents stated they didn’t know any pro-LGBT+ company. Furthermore, diversity management models were identified in the literature, such as the model for dissolution of differences, which is characterized by indifference to diversity, seeking standardization; the model for celebration of differences, which respects the LGBT+ community and comply with inclusion policies; and the model for learning and affectivity, an ideal model in which the organization recognizes and values each employee’s own individuality. In view of the above, it can be seen that there are ways to seek equality of conditions in work relations. It is up to companies to implement policies that go beyond mere discourse for diversity, thus transforming the work environment into a favorable place for minority groups.